Maracatu de baque solto : experiência do sagrado - Silva, João Ribeiro da (2013)
This thesis will analyze the experience of the sacred in Maracatu de Baque Solto Cambinda Brazilian, the city of Nazaré da Mata and Maracatu Estrela da Tarde City Glória do Goitá. The Rural Maracatu or Thump Loose arises in the historical context of the sugar crisis, the result of the decay of the devices and the emergence of the plants. Maracatu have in merging several groups and customs present in our culture, such as Coco, the Seahorse, the Ciranda the Mamulengo and Sao Goncalo Dance, but even being the result of reinterpretation of several of these elements, maracatu does not lose its nobleness and uniqueness. It is a cultural group that has deep relationships with popular religiosity and Catholic mother, especially with Jurema. In this sense it will seek to understand the experience of the sacred that permeates the performance of maracatu in their dance, the procession in their praises and wealth of its symbolic play.